PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI MIA SMA NEGERI 1 BANGUN PURBA TAHUN PEMBELAJARAN 2014/2015 - Fitri, Rena; Afifah, Nurul; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The purpose of this study was to determine the effect of cooperative learning model two stay two stray against student learning results biology class XI MIA SMA 1 Bangun Purba learning year 2014/2015. This type of research is a quasi-experiment. This study was conducted in November and December 2014. Data were analyzed using normality test, homogeneity and hypothesis testing. Experimental class averages 78.64 higher than the control class is 72.8. The results of this study can be concluded that by using the cooperative model of type two stay two stray can affect cognitive learning results of students in class XI MIA SMA Negeri 1 Bangun Purba 2014/2015 school year.